Fruit Fly Maggots as Alternative Feed to Improve Siamese Fighting Fish (Betta splendens) Fecundity, Eggs Hatchability and Fry Survivability - Chua KV, Chua KV; Tan SH, Tan SH; Liew JY, Liew; Hasnita CH (Universiti Malaysia Kelantan, 2017)
Siamese fighting fish or bettas are highly favoured for their aesthetical value and kept as ornamental fish. They are widely bred to satisfy the market demands. However, large-scale production of bettas is hampered by relatively high rate of mortality compared to the number of eggs laid. The nutrition intake literally influences the reproductive performance and eggs quality. Therefore, it is plausible to improve the survivability of betta fry through dietary manipulation. Bettas can be fed with variety of feeds. Bloodworms and the commercially available pellets are commonly used. Fruit fly maggots emerged as potential anti-infective agent and have been used as alternative fish feed. Therefore, this study aims to harness the beneficial properties of maggots to enhance the reproductive performance and increase the survivability of the bettas. The effects on fecundity, eggs hatchability and fry survivability of maggot feed were compared with the other common feed, namely bloodworms and commercial pellet. The results showed that maggots can serve as an alternative feed for bettas whereby it gave average hatchability rate of 65% and survivability rate of 69%. Although, the mean hatchability and survivability rate did not differ significantly from the other two feeds, this study suggests the attainable yet economic feeding material, has potential to inaugurate further studies to enhance the production of bettas in large scale.